2019
DOI: 10.31686/ijier.vol7.iss11.1888
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability in fertigated coffee yields and plant nutrients in soil saturation extracts

Abstract: The spatial distribution and levels of available plant nutrients (elements) in the soil can limit coffee yield and must be evaluated for effective crop management. Therefore, we analyzed spatial variability in yield and plant nutrients in the saturation extract of a clayey Oxisol cropped with fertigated coffee. The experiment was carried out on 14 hectares of coffee in Monte Carmelo, Minas Gerais, Brazil.  Soil samples were collected (0 - 0.2m layer) at 61 regular grid points (spaced 50x50m) and used to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In a research on the spatial variability in the productivity of fertigated coffee and plant nutrients in soil saturation extracts, Jorge et al (2019) used geostatistics to build a spatial variability model representing the physical attributes of the soil, finding that yield and soil chemistry varied across the study site. Thus, they concluded that maps generated from geostatistics can be useful tools for soil management in fertigated coffee plantations.…”
Section: Discussionmentioning
confidence: 99%
“…In a research on the spatial variability in the productivity of fertigated coffee and plant nutrients in soil saturation extracts, Jorge et al (2019) used geostatistics to build a spatial variability model representing the physical attributes of the soil, finding that yield and soil chemistry varied across the study site. Thus, they concluded that maps generated from geostatistics can be useful tools for soil management in fertigated coffee plantations.…”
Section: Discussionmentioning
confidence: 99%